International marketing agility and cost leadership strategies of frontier emerging market exporters in advanced economy markets - Khan, Huda; Khan, Zaheer; Knight, Gary (Elsevier, 2025)
Amid external crisis, cost-based strategies have become a growing concern for practitioners and an increasingly important area of scholarly inquiry. This is particularly true for frontier exporting firms from less advanced emerging markets (Pakistan), which often adopt cost-led strategies to succeed in the highly competitive and distinct environments of advanced economy markets. Despite its importance, the role of international marketing capabilities in driving these cost-based strategies has been largely overlooked in the existing literature. This study examines a sample of Pakistani exporting firms and demonstrates that international marketing agility, as a metadynamic capability, exerts both direct and indirect effects on business model innovation (BMI) through the mediation of cost leadership strategy when targeting advanced economy markets. Furthermore, environmental pressures positively moderate these relationships. The findings contribute to the dynamic capabilities perspective and highlight the crucial roles of international marketing agility and cost leadership strategy in supporting the BMI of exporting firms managing the complex and competitive environments of advanced economy markets. Additionally, the study provides valuable insights for emerging market exporting firms seeking to adapt and innovate their business models in response to the environmental pressure.
Keywords: international marketing agility; cost leadership strategy; environmental pressure; crisis; business model innovation; exporting firms; frontier emerging markets; fi=Kansainvälinen liiketoiminta|en=International Business|